Status Hukum Kepemilikan Hak Atas Tanah yang Tanahnya Telah Hilang Akibat Gempa Bumi di Cianjur - Putri, Catherina Amanda; Tjempaka, Tjempaka (Fakultas Syariah INSURI Ponorogo, 2023)
Proof of ownership of a plot of land is proven by the existence of a certificate and physical control so that if these two things are destroyed, the legal relationship between the owner and the land ends. There are several causes for the end of a person's land rights, one of which is that the land object has been destroyed due to a natural disaster. Because the term